Comparison of intravenous ketamine and fentanyl sedation in duration of mechanical ventilation in intensive care unit - Mishra, Raveesh; Pokharel, Krishna; Gautam, Alok Raj (Journal of Nepalese Society of Critical Care Medicine, 2024)
Background and aims: To compare the duration of mechanical ventilation in patients receiving ketamine compared to fentanyl for sedation in mechanically ventilated patients in intensive care unit.Methods: One hundred and six patients requiring mechanical ventilation were randomized to receive continuous intravenous infusion of either ketamine (1 mg/kg bolus followed by 0.4 to 0.8 mg/kg/h) or fentanyl (1mcg/kg bolus followed by 0.3-0.5 mcg/kg/min) with the dose titrated to achieve Richmond Agitation Sedation Scale (RASS) score of 0 to -1 and Behavioral Pain Scale (BPS) score of 3 to 7. The primary outcome was the duration of mechanical ventilation. Secondary outcomes were sedation score, analgesia score and need of vasopressors.Results: The mean duration of ventilation was 2.5±0.6 days and 2.2±1.0 days (p=0.1) in patients receiving ketamine and fentanyl respectively. More patients required vasopressors: 27 (50.9%) vs 9 (17%) in patients receiving fentanyl compared to ketamine (p